التنظيم التشريعي للوعد بالتفضيل: دراسة مقارنة - الحياري، أحمد إبراهيم حسين (جامعة مؤتة - عمادة البحث العلمي, 2016)
This research deals with the provisions of the promise of preference in article (1123) of French the Civil Code, as amended by Decree No. 131-2016 dated 10/02/2016. In this amendment the French legislator adopts the previous jurisprudence concerning the conditions of this contract. This amendment shall remove the controversy revolving around some judicial decisions on the matter, particularly those that affect the scope of the obligations of the promising and the penalty resulting from the breach there from. If the promising concludes the promised contact with another person, the amended article 1123 gives the beneficiary of the promise the right to seek compensation. In special cases, he/she will be able also to annul this contract or replacing the third party. The researcher tackles the necessity to regulate the promise of preference in the Jordanian Civil Law. He points out that the provisions relating to the promise to contract do not accommodate the promise of preference and thus there is a need to develop a new text to address this matter. This provision should define the conditions of this contact and imposes the compensation as a penalty for violation of those conditions. Furthermore, the researcher suggests the modification of the article (106) of the Jordanian Civil Law by adding a paragraph which requires the invalidity of the contract concluding with a third party during the period of the promise, if he knows the existence of the promise.
تناول هذا البحث أحكام الوعد بالتفضيل كما كرسها المشرع الفرنسي في المادة (1123) من القانون المدني بصيغتها المعدلة بالمرسوم رقم131-2016 الصادر بتاريخ 10/2/2016، حيث بين الباحث أن المشرع الفرنسي تبنى الاجتهادات القضائية السابقة المتعلقة بشروط صحة الوعد بالتفضيل وأزال الجدل حول بعض الحلول القضائية المتعلقة بآثار هذا العقد؛ فحدد نطاق الالتزامات المترتبة على الواعد والجزاء المترتب على الإخلال بها؛ فقضى بحق المستفيد من الوعد بالمطالبة بالتعويض، كما منحه الحق بالمطالبة بإبطال العقد المبرم مع الغير أو الحول محله فيه في حالات خاصة. كما تناول الباحث الحاجة إلى تنظيم الوعد بالتفضيل في القانون المدني الأردني؛ فأوضح بأن النصوص المتعلقة بالوعد بالتعاقد لا تستوعب الوعد بالتفضيل، وأن هناك ضرورة لاستحداث نص جديد يعالج موضوع الوعد بالتفضيل في القانون المدني الأردني، يحدد شروطه ويرتب التعويض على مخالفة تلك الشروط. كما رأى الباحث أن هناك حاجة لتعديل المادة (106) من هذا القانون بإضافة فقرة تقضي ببطلان العقد الموعود في حال إبرامه مع غير المستفيد خلال مدة الوعد، متى كان الغير عالماً بوجود الوعد.
Keywords: لوعد بالتفضيل -- الوعد بالتعاقد -- القانون المدني الأردني -- القانون المدني الفرنسي